2021
DOI: 10.1002/casp.2566
|View full text |Cite
|
Sign up to set email alerts
|

Sense of responsible togetherness, sense of community, and civic engagement behaviours: Disentangling an active and engaged citizenship

Abstract: Local communities should represent entities where individuals get answers to their affiliation needs and for which they feel responsible, but in modern ones, increasingly complex ways of living together are fostering citizens' civic and social disengagement. The present study addresses the relationships between the cognitive, affective, and behavioural components of an active and engaged citizenship. Five hundred and fifty-five Italian citizens answered an online questionnaire about their Sense of Responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Therefore, a sense of community was replaced by connectedness and trust (Di Napoli, Dolce, et al, 2019), while empowerment and social participation were represented by shared and social action. Our decision is supported by the importance that Velázquez et al (2017) assigned to connectedness in emergencies, by recent contributions on the sense of community and togetherness (Procentese & Gatti, 2021), and prosocial behavior in pandemics (Aresi et al, 2021) and by the findings of our research in Italy (Di Napoli et al, 2021; Marzana et al, 2021; Migliorini et al., 2021; Procentese et al, 2021), which was published in 2021. Finally, following the definition process, we conducted a systematic review using the keywords: trust, connectedness, resilience, shared action, social action, individual well-being, and social well-being (see Figure 1).…”
Section: Methodsmentioning
confidence: 52%
“…Therefore, a sense of community was replaced by connectedness and trust (Di Napoli, Dolce, et al, 2019), while empowerment and social participation were represented by shared and social action. Our decision is supported by the importance that Velázquez et al (2017) assigned to connectedness in emergencies, by recent contributions on the sense of community and togetherness (Procentese & Gatti, 2021), and prosocial behavior in pandemics (Aresi et al, 2021) and by the findings of our research in Italy (Di Napoli et al, 2021; Marzana et al, 2021; Migliorini et al., 2021; Procentese et al, 2021), which was published in 2021. Finally, following the definition process, we conducted a systematic review using the keywords: trust, connectedness, resilience, shared action, social action, individual well-being, and social well-being (see Figure 1).…”
Section: Methodsmentioning
confidence: 52%
“…Responses for items ranged from 1 � strongly disagree to 5 � strongly agree on a 5-pointLikert-type scale. A composite mean score of 2.5 and above indicated higher levels of rural ft. Studies have used the tool and have reported Cronbach's alpha between 0.75 and 0.85 [25]; in this study, it was 0.79.…”
Section: Rural Fitmentioning
confidence: 61%
“…For example, Bowe et al (2022) found coordinated local community helping to be associated with increased sense of community and well-being. Additionally, Procentese and Gatti (2022) showed that actively taking on responsibilities and engaging in local relationships and communal activities are linked with a stronger sense of community.…”
Section: Empirical Evidence On Sense Of Communitymentioning
confidence: 99%
“…We grounded our study on theoretical perspectives of the need-to-belong theory (Baumeister, 2012;Baumeister & Leary, 1995) and sense of community theory (McMillan & Chavis, 1986). According to prior research, neighbourhood engagement (Albanesi et al, 2007;Bowe et al, 2022;Mannarini & Fedi, 2009;Procentese & Gatti, 2022;Talò et al, 2014;Tang et al, 2017) and perceived residential environment pleasantness (Bond et al, 2012;Brown et al, 2009;Latikka et al, 2023;Rugel et al, 2019;Wood et al, 2012) have emerged as predictors of a sense of community in cross-sectional contexts.…”
Section: This Studymentioning
confidence: 99%